Comparison of single dose cefuroxime and multiple dose ceftriazone in elective caesarean section - Raval, Ravi; Shrivastava, Sweta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Caesarean section is a major life saving surgical procedure for mother and baby. The objective of this study to evaluate the efficacy of single dose of 1.5 gm of cefuroxime as prophylactic antibiotic compared to multiple doses of ceftriaxone in elective caesarean section in reducing postoperative morbidity. Methods: This is an observational study conducted at tertiary care teaching hospital. A total of 434 cases were included from January 2017 to September 2018. One group of patients were given single dose cefuroxime 1.5 gm intravenously 30 minutes before the surgery as prophylactic antibiotic. Other group include those patients who have been operated for elective caesarean section before this existing antibiotic policy, where multiple doses of ceftriaxone 1 gm intravenously 12 hourly for 7 days were given as per policy of that time. A data collection forms were designed to record information about every patient including comprehensive history, examination, investigations, intra-operative events and post-operative follow-up course. Results: In cefuroxime group 3.7% and in ceftriaxone group 4.6% had wound discharge. Both the groups had 2.8% of wound dehiscence. In cefuroxime group, 0.9%had other infections like upper respiratory tract infections/urinary tract infections (URTI/UTI), whereas in ceftriaxone group 2.3% patients had other infections. In cefuroxime group 4.1% patients and in ceftriaxone group 6% patients had extended hospital stay. Conclusions: This study supports that single dose of cefuroxime can replace multiple doses of other antibiotics as prophylaxis for post caesarean section infection with reducing infectious morbidity in a cost-effective manner.